In Emergency Department Patients with Acute Chest Pain, Stress Cardiac MRI Observation Unit Care Reduces 1- year Cardiac-Related Health Care Expenditures: A Randomized Trial - Miller, Chadwick D. (2011)
OBJECTIVE: To compare the direct cost of medical care and clinical events during the first year after patients with intermediate risk acute chest pain were randomized to stress cardiovascular magnetic resonance (CMR) observation unit (OU) testing, versus inpatient care. BACKGROUND: In a recent study, randomization to OU-CMR reduced median index hospitalization cost compared to inpatient care in patients presenting to the emergency department with intermediate risk acute chest pain. METHODS: Emergency department patients with intermediate risk chest pain were randomized to OU-CMR (OU care, cardiac markers, stress CMR) or inpatient care (admission, care per admitting provider). This analysis reports the direct cost of cardiac-related care and clinical outcomes (MI, revascularization, cardiovascular death) during the first year of follow-up subsequent to discharge. Consistent with health economics literature, provider cost was calculated from work-related relative value units using the Medicare conversion factor; facility charges were converted to cost using departmental specific cost-to-charge ratios. Linear models were used to compare cost accumulation among study groups. RESULTS: One-hundred nine (109) randomized subjects were included in this analysis (52 OU-CMR, 57 inpatient care). The median age was 56 years; baseline characteristics were similar in both groups. At 1 year, 6% of OU-CMR and 9% of inpatient care participants experienced a major cardiac event (p=0.72) with 1 patient in each group experiencing a cardiac event after discharge. First-year cardiac-related costs were significantly lower for participants randomized to OU-CMR compared to participants receiving inpatient care (geometric mean = $3101 vs $4742 including the index visit (p = .004) and $29 vs $152 following discharge (p = .012)). During the year following randomization, 6% of OU-CMR and 9% of inpatient care participants experienced a major cardiac event (p=0.72). CONCLUSIONS: An OU-CMR strategy reduces cardiac-related cost of medical care during the index visit and over the first year subsequent to discharge, without an observed increase in major cardiac events.